Answer:
the answer would be 210:40
Step-by-step explanation:
Answer:A:0
Step-by-step explanation:hope this helps :)
x^2-9x-6=0
Use the quadratic formula to get (9+sqrt(105))/2 or (9-sqrt(105))/2
Answer:
x = (2 i π n)/log(4) + log(2 sqrt(2))/log(4) for n element Z
Step-by-step explanation:
Solve for x:
2 sqrt(2) = 4^x
Hint: | Reverse the equality in 2 sqrt(2) = 4^x in order to isolate x to the left hand side.
2 sqrt(2) = 4^x is equivalent to 4^x = 2 sqrt(2):
4^x = 2 sqrt(2)
Hint: | Eliminate the exponential from the left hand side.
Take the logarithm base 4 of both sides:
Answer:x = (2 i π n)/log(4) + log(2 sqrt(2))/log(4) for n element Z